Removal of hexavalent chromium Cr (VI) using activated carbon prepared from mango kernel activated with H3PO4 - Rai M. K.; Shahi G.; Meena V.; Meena R.; Chakraborty S.; Singh R. S.; Rai B. N. (2016, 2016)
Title screen